Triacylglycerols containing branched palmitic acid ester of hydroxystearic acid (PAHSA) are present in the breast milk and hydrolyzed by carboxyl ester lipase - Brejchova, Kristyna; Paluchova, Veronika; Brezinova, Marie; Cajka, Tomas; Balas, Laurence; Durand, Thierry; Krizova, Marcela; Stranak, Zbynek; Kuda, Ondrej (Food chemistry, 2022)
Breast milk is a complex mixture containing underexplored bioactive lipids. We performed an observational case-control study to compare the impact of delivery mode: caesarean section (CS) and vaginal birth (VB); and term (preterm and term delivery) on the levels of lipokines in human milk at different stages of lactation. Metabolomic analysis of the milk identified triacylglycerol estolides as a metabolic reservoir of the anti-inflammatory lipid mediator 5-palmitic acid ester of hydroxystearic acid (5-PAHSA). We found that triacylglycerol estolides were substrates of carboxyl ester lipase and 5-PAHSA-containing lipids were the least preferred substrates among tested triacylglycerol estolide isomers. This explained exceptionally high colostrum levels of 5-PAHSA in the VB group. CS and preterm birth negatively affected colostrum lipidome, including 5-PAHSA levels, but the lipidomic profiles normalized in mature milk. Mothers delivering term babies vaginally produce colostrum rich in 5-PAHSA, which could contribute to the prevention of intestinal inflammation in newborns.
Keywords: Esters; Infant; estery; laktace; Milk, Human; Preterm birth; Pregnancy; kolostrum; lidé; kyselina palmitová; Humans; triglyceridy; Lipase; PAHSA; novorozenec; Triglycerides; lipasa; Palmitic Acid; Elective caesarean section; kojenec; Lactation; předčasný porod; Case-Control Studies; císařský řez; ženské pohlaví; Cesarean Section; Human breast milk; těhotenství; Female; studie případů a kontrol; Premature Birth; Colostrum; Lipidomics; Infant, Newborn; mateřské mléko